Design and Demonstration of Tunable Amplified Sensitivity of AlGaN/GaN High Electron Mobility Transistor (HEMT)-Based Biosensors in Human Serum - Tai, Tse-Yu; Sinha, Anirban; Sarangadharan, Indu; Pulikkathodi, Anil Kumar; Wang, Shin-Li; Lee, Geng-Yen; Chyi, Jen-Inn; Shiesh, Shu-Chu; Lee, Gwo-Bin; Wang, Yu-Lin (Analytical chemistry (Washington), 2019)
We have developed a swift and simplistic protein immunoassay using aptamer functionalized AlGaN/GaN high electron mobility transistors (HEMTs). The unique design of the sensor facilitates protein detection in a physiological salt environment overcoming charge screening effects, without requiring sample preprocessing. This study reports a tunable and amplified sensitivity of solution-gated electric double layer (EDL) HEMT-based biosensors, which demonstrates significantly enhanced sensitivity by designing a smaller gap between the gate electrode and the detection, and by operating at higher gate voltage. Sensitivity is calculated by quantifying NT-proBNP, a clinical biomarker of heart failure, in buffer and untreated human serum samples. The biosensor depicts elevated sensitivity and high selectivity. Furthermore, detailed investigation of the amplified sensitivity in an increased ionic strength environment is conducted, and it is revealed that a high sensitivity of 80.54 mV/decade protein concentration can be achieved, which is much higher than that of previously reported FET biosensors. This sensor technology demonstrates immense potential in developing surface affinity sensors for clinical diagnostics.